Impact of Cell Therapy on Myocardial Perfusion and Cardiovascular Outcomes in Patients With Angina Refractory to Medical Therapy: A Systematic Review and Meta-Analysis. Issue 6 (18th March 2016) - Khan, Abdur Rahman; Farid, Talha A.; Pathan, Asif; Tripathi, Avnish; Ghafghazi, Shahab; Wysoczynski, Marcin; Bolli, Roberto
Abstract : Rationale: : The effect of stem/progenitor cells on myocardial perfusion and clinical outcomes in patients with refractory angina remains unclear because studies published to date have been small phase I–II trials. Objective: : We performed a meta-analysis of randomized controlled trials to evaluate the effect of cell-based therapy in patients with refractory angina who were ineligible for coronary revascularization. Methods and Results: : Several data sources were searched from inception to September 2015, which yielded 6 studies. The outcomes pooled were indices of angina (anginal episodes, Canadian Cardiovascular Society angina class, exercise tolerance, and antianginal medications), myocardial perfusion, and clinical end points. We combined the reported clinical outcomes (myocardial infarction, cardiac-related hospitalization, and mortality) into a composite end point (major adverse cardiac events). Mean difference (MD), standardized mean differences, or odds ratio were calculated to assess relevant outcomes. Our analysis shows an improvement in anginal episodes (MD, −7.81; 95% confidence interval [CI], −15.22 to −0.41), use of antianginal medications (standardized MD, −0.59; 95% CI, −1.03 to −0.14), Canadian Cardiovascular Society class (MD, −0.58; 95% CI, −1.00 to −0.16), exercise tolerance (standardized MD, 0.331; 95% CI, 0.08 to 0.55), and myocardial perfusion (standardized MD, −0.49; 95% CI, −0.76 to −0.21) and a decreased risk of major adverse cardiac events (odds ratio, 0.49; 95% CI, 0.25 to 0.98) and arrhythmias (odds ratio, 0.25; 95% CI, 0.06 to 0.98) in cell-treated patients when compared with patients on maximal medical therapy. Conclusions: : The present meta-analysis indicates that cell-based therapies are not only safe but also lead to an improvement in indices of angina, relevant clinical outcomes, and myocardial perfusion in patients with refractory angina. These encouraging results suggest that larger, phase III randomized controlled trials are in order to conclusively determine the effect of stem/progenitor cells in refractory angina. Abstract : Supplemental Digital Content is available in the text.